Prevalence and factors associated with regular fast-food consumption among the adult population in Qatar: cross-sectional analysis from Qatar Biobank cohort - Massarweh, Alaa Zuhair; Kennedy, Lynne Alexandra; Saleh, Asayel; Al-Thani, Aljazi; Al Rajabi, Ala (Frontiers in Nutrition, 2026)
BackgroundThe Eastern Mediterranean Region has undergone a rapid nutrition transition over the last three decades, with healthier traditional table diets displaced by energy-dense convenience foods. To the best of our knowledge, this is the first large cohort-based estimate of regular fast-food consumption (RFFC ≥1 time/week) and its correlates among the adult population in Qatar using Qatar Biobank, a volunteer prospective cohort of Qataris and long-term residents.MethodsA cross-sectional study using a simple randomized sample of 2,000 adult participants from the Qatar Biobank (QBB) longitudinal cohort. Dietary intake was assessed using a validated food-frequency questionnaire. RFFC was modeled as a binary outcome using purposeful multivariable logistic regression with an age*sex interaction. A sensitivity analysis on a sub-cohort population to examine the impact of job-related factors.ResultsRFFC was highly prevalent among participants, with 49.7% reporting frequently consuming fast food (≥1 time/week). Age emerged as the strongest independent predictor that was modified by sex (likelihood-ratio test, p = 0.034), with the youngest adults (18–24 years) having four-fold higher odds of RFFC compared to the oldest cohort (45–65 years; AORs = 4.36, 95% CI: 2.37–8.02). A significant age–sex interaction was discovered, showing that young women (18–24) had particularly high predicted probabilities of RFFC (78%), which was less than that of their male counterparts by mid-adulthood and reversed slightly in older ages. Low fruit/vegetable intake was significantly associated with RFFC (AOR = 1.30, 95% CI: 1.30–1.60). However, education was positively associated in crude models but lost its significance after adjusting for other covariates and accounting for age–sex interaction. In the sub-cohort population (sensitivity analysis restricted to employed only, n = 1,660), night shift schedules were significantly associated with 40% higher odds of RFFC (AOR = 1.40, 95% CI: 1.09–1.81), the age–sex interaction persisted, and low fruit/vegetable intake remained significantly predictive (AOR = 1.37, 95% CI: 1.10–1.71).ConclusionRFFC is highly prevalent in this large longitudinal, phenotyped sample of adults residing in Qatar and is concentrated among younger adults, particularly women with low fruit/vegetable intake and among those engaged in night-shift work. These findings highlight the need for age- and sex-specific, as well as occupationally targeted, dietary interventions and food environment strategies to facilitate healthier choices.